2015
DOI: 10.1038/srep11563
|View full text |Cite
|
Sign up to set email alerts
|

Altered baseline brain activity differentiates regional mechanisms subserving biological and psychological alterations in obese men

Abstract: Obesity as a chronic disease is a major factor for insulin resistance and Type 2 diabetes, which has become a global health problem. In the present study, we used resting state functional MRI to investigate the amplitude of low frequency fluctuations of spontaneous signal during both hunger and satiety states in 20 lean and 20 obese males. We found that, before food intake, obese men had significantly greater baseline activity in the precuneus and lesser activity in dorsal anterior cingulate cortex (dACC) rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… Kullmann et al (2013a) found that intranasal insulin application induced increased activation in hypothalamus. Furthermore, our previous functional MRI study showed that the negative correlation between plasma insulin and the regional brain activity ( Zhang et al, 2015a ). However, there is no study investigating the relationship between the GMV of the region related to obesity and plasma insulin.…”
Section: Introductionmentioning
confidence: 99%
“… Kullmann et al (2013a) found that intranasal insulin application induced increased activation in hypothalamus. Furthermore, our previous functional MRI study showed that the negative correlation between plasma insulin and the regional brain activity ( Zhang et al, 2015a ). However, there is no study investigating the relationship between the GMV of the region related to obesity and plasma insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in resting-state activity have been shown between obese and normal weight cohorts (Fox & Raichle, 2007;Kullmann et al, 2012;Garc ıa-Garc ıa et al, 2013). Moreover, rsfMRI, in combination with structural imaging methods, has been used as a predictive measure for body-mass index (BMI) (Park et al, 2015), and has implicated brain regions important for cognitive control, motivation, reward, salience and inhibition as important in the neuropathology of obesity (McFadden et al, 2013;Lips et al, 2014;Dong et al, 2015;Lepping et al, 2015;Zhang et al, 2015a). Most of these studies, however, concern only one time point, and fewer have studied the treatment effect of bariatric surgery (Frank et al, 2014;Lepping et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After ingestion of a sucrose solution, obese females had differential connectivity patterns between the hypothalamus and reward-/ gustatory-associated brain regions compared to lean females (Kilpatrick et al, 2014). Comparing scans in pre-and postprandial states, a study in obese versus normal-weight males found the obese had increased resting-state activity in the putamen and decreased activity in the orbitofrontal cortex and medial frontal cortex, but these differences were not found in the postprandial state (Zhang et al, 2015a). A somewhat similar study in females also found the obese had increased resting-state activity in the putamen, claustrum and insula compared to normal-weight controls, but that food intake had no modulating effect on resting-state activity (Hogenkamp et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of work has shown that in persons with obesity, areas and neuronal networks involved in energy regulation, both in homeostatic and hedonic areas such as the hypothalamus, insula, cingulate and orbitofrontal cortex (OFC), function differently compared with lean subjects . Generally, in persons with obesity, brain connectivity and activity in these (sub)cortical brain areas and neuronal networks are increased . In addition to changes in functional connectivity, structural connectivity is also associated with an elevated body mass index (BMI) .…”
Section: Introductionmentioning
confidence: 99%